Current Trends of Poisoning Cases Admitted at Tertiary Care Hospital - Avinash H. Waghmode; Prakash Mohite; Sudhir Ninave; Pravir Bodkha; Sonali Kotkar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acute poisoning is important medical emergency and one of the cause of death. A thorough knowledge of the profile of the victim is essential for management and prevention of poisoning. A prospective analysis of all poisoning cases admitted to BKL Walawalkar Hospital, Sawarde was done to study the pattern of poisoning reported. 186 cases of poisoning including snake bite and scorpion bite were admitted. Data on age, sex, marital status, type of poison, time of exposure, mode of poison and outcome of poisoning were recorded and analysed. There are 111 males and 75 females victim involved in the study. Most common manner of poisoning was Accidental. Most common age group found was 1-10 year followed by 21-30 year. Majority of the victims were Married. Out of all 186 cases admitted 133 were recoverd, 48 had taken Discharge Against Medical Advice (DAMA) and 2 died and 2 were referred.